RETRACTED: Impact of Abusive Supervision on Psychological Engagement and Absorptive Capacity Among Students: Mediating Role of Knowledge Hiding - Zhang, Xiyun; Yu, Jiawen (Frontiers in Psychology, 2022)
The research aimed to estimate the direct impact of abusive supervision and knowledge hiding on psychological engagement and absorptive capacity. It also explored the knowledge hiding as a mediator. This survey study was a cross-sectional one. The data were collected from employees from four different sectors through a questionnaire. The random convenient sampling type was managed for sampling. The data were collected from 415 employees. Structural equation modeling (SEM) was used as a data analysis technique. Because the two-stage SEM technique produces precise and accurate estimates while modeling the path analysis. The output of the measurement model assessment confirmed that all measurement scales were reliable. Besides, the structural model assessment confirmed that abusive supervision did not significantly predict the absorptive capacity and psychological engagement however knowledge hiding negatively predicted the psychological engagement and abusive supervisory behavior. The outcome revealed a negative full mediation approved of knowledge hiding between abusive supervisory behavior, psychological engagement and absorptive capacity. Therefore, abusive supervision and knowledge adversely influenced the psychological engagement and absorptive capacity at the workplace.